Maxillofacial Imaging - Larheim, Tore A. (Springer International Publishing, 2018)
This book demonstrates how advanced medical imaging techniques can be successfully applied to dental and maxillofacial conditions. There is a focus on CT and MRI, but the use of all contemporary imaging techniques are illustrated including PET, PET/CT, ultrasonography, and cone beam CT. The presentation is in atlas style, with succinct, bulleted text and a wealth of high-quality images in multiple planes. All images for each patient are grouped to enable the reader very quickly to gain an imaging overview of the condition under consideration. After a comprehensive introductory chapter on normal imaging anatomy, the role of advanced imaging techniques is described in pathologic conditions of the mandible and maxilla, temporomandibular joint, regions closely related to the jaw, paranasal sinuses, oral cavity, salivary glands, and structures adjacent to the maxillofacial region. A concluding chapter examines the use of interventional procedures for diagnosis and treatment of maxillofacial conditions. Compared with the first edition, numerous additional cases have been incorporated and a completely new chapter focuses on cone beam CT. The book will be useful for oral and maxillofacial radiologists, oral and maxillofacial surgeons, dentists, radiologists, plastic surgeons, head and neck surgeons, and others who work with maxillofacial conditions.